Bamboo-like carbonitride nanotubes with multi-type active sites for oxygen reduction reaction in both alkaline and acid mediums. (8th February 2022) - Yan, Jitong; Liu, Yanyan; Wang, Runan; Xia, Meirong; Wang, Jing; Gao, Faming; Tang, Yongfu
Abstract: To omni-directionally utilize carbon-based material in nanoscale and improve its catalytic activity for oxygen reduction reaction (ORR), bamboo-like carbonitride nanotubes (bCNTs) with high-density multi-type active sites (CoO@Co–N-bCNT) are facilely synthesized via a multi-step method referring to thermal pyrolysis of Co 2+ complexed melamine, acid leaching and second annealing. Multi-type active sites including encapsulated Co nanoparticles, intercalated Co/CoO species, Co-Nx coordinated sites and defect-rich surface are present in the as-prepared CoO@Co–N-bCNT electrocatalyst. The types and densities of these active sites are easily tuned via the ratio of melamine to Co 2+ in precursors and subsequent treatment. Due to the high-density multi-type active sites and bamboo-like tubular structure, CoO@Co–N-bCNT electrocatalyst exhibits high catalytic activity for ORR with high stability in both alkaline and acid electrolytes. Quasi-solid-state zinc air battery (ZAB) assembled with the CoO@Co–N-bCNT as the cathode exhibits open circle voltage of 1.39 V and peak power density of 14.9 mW cm −2 . Two-cell series of quasi-solid-state ZABs can light LED indicator for 7 h, suggesting its promising practical application. The studies provide facile strategy to design the carbon-based electrocatalysts with high performance and tune their active sites. Graphical abstract: Image 1 Highlights: Multi-type active sites for ORR in one material were constructed via a facile method. The annealing process after acid leaching improves the catalytic performance. The as-prepared electrocatalysts exhibit high catalytic activity for ORR due to high-density multi-type active sites. It is promising for the application of the as-prepared electrocatalysts in both PEMFCs and ZABs.